Mode and Associated Injury among the Patients Presented with Acute Subdural Hematoma (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Different mode of injuries are responsible for the formation of acute subdural hematoma.Objective: The purpose of the present study was to mode and associated injury among the patients presented with acute subdural hematoma.Methodology: This cross-sectional study was carried out in the Neurosurgery Department of Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2011 to August 2012 for a period of one year and eight months. Patients with acute subdural hematoma who fulfil the inclusion criteria for surgery and got admitted into the Hospital were selected as study population. Acute Subdural hematoma patient of any age, both sexes with GCS 5 to 13, thickness of hematoma more than l0 mm, midline shift more than 5 mm, pupil reacting to light and patient presented within 72 hours of injury were included for this study. At admission, a detailed history of the illness was taken from the patient or attendant, thorough general and neurological examinations were carried out and were recorded.Results: A total number of 48 patients presented with acute subdural hematoma who were operated in the Department of Neurosurgery of Dhaka Medical College & Hospital, Dhaka, Bangladesh were included in current study. Majority of the patients were in the age group of 10 to 30 years which was 25(52.1%) cases. In this study, majority of patients 26(54.2%) had history of road traffic accidents. Other causes of injury were fall from height 9(18.75%), physical assault 7(14.58%), industrial accident 2(4.16%). No associated injury was found in 18(37.5%) patients and 15(31.2%) cases were hemorrhagic contusion. In this study 3(6.5%) cases were presented with intra-cerebral hemorrhage (ICH) and 4(8.3%) cases were associated EDH. SAH was found in 3(6.5%) cases.Conclusion: In conclusion the most common mode of injury is road traffic accidents which is associated with hemorrhagic contusion.Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):8-11